Warrior Scientist: Star Trek: Voyager’s Chakotay and American Indian Television Representation - Macías, Anthony (AMERICANA E-journal of American Studies in Hungary, 2022)
The essay analyzes the Native American character, Chakotay, played by Mexican American actor Robert Beltran, from the multicultural ensemble television series Star Trek: Voyager (1995-2001). After acknowledging “indigenous futurism” in speculative fiction and film, I trace this exoticized Indigenous cosmonaut character’s televisual regulator/enforcer “good Indian” antecedents. Although American Indians in feature films and TV programs traditionally appeared in Westerns, symbolically relegated to the margins of America’s allegorical usable past, in Gene Roddenberry’s future utopian meritocracy, Indigenous peoples have not vanished. I therefore situate such rare characters in the Star Trek pop culture canon, then examine in depth Commander Chakotay, a former outlaw resistance fighter, who serves Starfleet, which tolerates diversity while exporting the colorblind colonialism of the United Federation of Planets. In addition to incorporating secondary research on First Nations viewer responses, I advance an original argument about how Voyager’s non-Native creators signified Chakotay’s Indianness with the pan-ethnic trappings of tribalism, for the hokum of Hollywood in an inclusive, post-racial deep space “final frontier.” With his indistinct indigeneity, Commander Chakotay is complex but ungrounded; an officer and a gentleman; a twenty fourth-century amateur Anthropologist; a liberal fantasy; a warrior scientist. I conclude that negative and supposedly positive stereotypes perform ideological work legitimizing racial hierarchy and justifying structural stratification.